(untitled) (Agroindustria, Sociedad y Ambiente, 2016)
Climate change along with its recent presence in the various political and public arenas in modern times is part of a great epistemological complexity; where the content that scientific disciplines have studied and studied separately condensed, in addition to the resulting links that have generated a new architecture of questions and challenges conventional wisdom currently available. The development of educational programs and the dissemination of information on climate change is a mandate established in Articles 4 and 6 of the UN Framework Convention on Climate Change (UNFCCC), which refers to the need to develop efforts in regarding access to information, awareness, education, training, participation and international cooperation on Climate Change. In light of the above a new vision for the issue of climate change and adaptation to the work plan Article 6 of the United Nations Framework Convention on an educational proposal adapted to local experiences is proposed.